Stimulating Creativity: A Systematic Literature Review on Students’ Engagement and Cognitive Development through Creative Writing - Sudirman, Anselmus (Langkawi: Journal of The Association for Arabic and English, 2025)
Creative writing provides an effective framework for cultivating fundamental values in educational environments, hence improving student engagement, creativity, and cognitive growth.  This study integrates findings from several academic sources to clarify how creative writing promotes values, including self-expression, critical thinking, inclusion, and cultural understanding.  Integrating process-oriented and reflective skills, creative writing fosters cognitive and emotional development.  Ethnographic and cross-cultural studies demonstrate its adaptability across many cultural and educational contexts, emphasizing the significance of context-specific methodologies. Obstacles, including inadequate teacher preparation and inflexible curriculum frameworks, hinder the successful implementation of these values.  Recommendations encompass the enhancement of teacher training programs, the building of flexible curricula, the cultivation of supportive settings, and the commitment to ongoing research and adaptation.  Ultimately, creative writing serves as an effective instrument for nurturing fundamental educational principles and promoting an inclusive and contemplative learning atmosphere.  As educational environments transform, a steadfast dedication to these principles is essential for adjusting creative writing methodologies to address varied student requirements, thereby guaranteeing its lasting influence on global education.